2023
DOI: 10.1002/jmv.29303
|View full text |Cite
|
Sign up to set email alerts
|

Live‐virus serum neutralization after bivalent SARS‐CoV‐2 mRNA vaccination in hemodialysis patients

Louise Benning,
Marie Bartenschlager,
Heeyoung Kim
et al.

Abstract: The development of bivalent booster vaccines addresses the ongoing evolution of the emerging B.1.1.529 (omicron) variant subtypes that are known to escape vaccine‐induced neutralizing antibody response. Little is known about the immunogenicity and reactogenicity of bivalent mRNA vaccines in hemodialysis patients with impaired vaccine response. In this prospective, observational cohort study, we analyzed SARS‐CoV‐2 anti‐S1 IgG, surrogate neutralizing antibodies (SNA), and live‐virus neutralization against the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Another recent publication by Huth et al showed an increase in the neutralization of variants BA.4 and BA.5 in infection-naïve hemodialysis patients after the fifth vaccination with a bivalent BA.4-5-adapted vaccine [ 21 ]. This was also observed in a study by Benning et al, however, without an increase in humoral immunity in those patients with a prior SARS-CoV-2 infection [ 22 ].…”
Section: Discussionsupporting
confidence: 76%
“…Another recent publication by Huth et al showed an increase in the neutralization of variants BA.4 and BA.5 in infection-naïve hemodialysis patients after the fifth vaccination with a bivalent BA.4-5-adapted vaccine [ 21 ]. This was also observed in a study by Benning et al, however, without an increase in humoral immunity in those patients with a prior SARS-CoV-2 infection [ 22 ].…”
Section: Discussionsupporting
confidence: 76%